2021
DOI: 10.3390/molecules26247413
|View full text |Cite
|
Sign up to set email alerts
|

Surface Pretreatments of AA5083 Aluminum Alloy with Enhanced Corrosion Protection for Cerium-Based Conversion Coatings Application: Combined Experimental and Computational Analysis

Abstract: The effects of surface pretreatments on the cerium-based conversion coating applied on an AA5083 aluminum alloy were investigated using a combination of scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), polarization testing, and electrochemical impedance spectroscopy. Two steps of pretreatments containing acidic or alkaline solutions were applied to the surface to study the effects of surface pretreatments. Among the pretreated samples, the sample prepared by the pretreatment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The samples fabricated with novel Aluminium are experimentally tested for the surface hardness (dependent variable) evaluated for all the three sample groups using statistical analysis are plotted in the given bar graph as shown in Fig. 8 [49]. The results revealed that reinforced hybrid composites have a significantly high hardness than those without reinforcement [50].…”
Section: Hardness Testing Resultsmentioning
confidence: 99%
“…The samples fabricated with novel Aluminium are experimentally tested for the surface hardness (dependent variable) evaluated for all the three sample groups using statistical analysis are plotted in the given bar graph as shown in Fig. 8 [49]. The results revealed that reinforced hybrid composites have a significantly high hardness than those without reinforcement [50].…”
Section: Hardness Testing Resultsmentioning
confidence: 99%
“…By contrast, the curve of the coated-ZA samples shows a shift in the direction of positive E corr and negative I corr . Higher E corr indicates lower corrosion probability, whereas higher I corr represents a faster corrosion rate [ 33 , 34 ]. As shown in Table 2 , the I corr value of the bare-ZA is one order of magnitude higher than that of the coated-ZA sample.…”
Section: Resultsmentioning
confidence: 99%